Evaluation of extension support within comprehensive agricultural support program in the Tshwane Metropolitan Municipality - Mafsikaneng, Ntau Anton (University of Limpopo, 2015)
The study was undertaken to understand the beneficiary and non–beneficiary evaluation of the CASP-Extension programme and how it can be used to improve future programme delivery. This study was conducted in the City of Tshwane Metropolitan Municipality between October 2014 and February 2015. In this study a survey design was used. The study used both qualitative and quantitative methods. Data for this study were gathered through semi–structured questionnaires. The respondents of this study included sixty farmers made up of LRAD farmers receiving CASP-Extension and those not receiving CASP-Extension. The farmers were chosen by systematic sampling. Independent t-test and Chi-Squared tests were applied to analyse the data using Statistical Package for Social Sciences (SPSS). The results revealed that receiving CASP-Extension support does not contribute to yield increase over non-recipients. Regarding participation in CASP-Extension, recipients of CASP-Extension support indicated receiving at one visit by Extension agent per month which is slightly less than what the literature suggests. The image of CASP-Extension as perceived by Non-CASP-Extension recipients is a poor one compared with a good image painted by CASP-Extension recipients. This notwithstanding, most Non-CASP-Extension recipients have the ambition to receive CASP-Extension support. CASP-Extension could improve its image amongst Non-CASP-Extension recipients by addressing the areas of dissatisfaction indicated by respondents in the study. KEY CONCEPTS Comprehensive Agricultural Support Programme; Evaluation; Land Redistribution of Agricultural Development; Extension
Thesis (M.Sc. (Agricultural Extension)) -- University of Limpopo, 2015
Keywords: Comprehensive agricultural support program; Land Redistribution of Agricultural Development; Land reform -- South Africa